Personality development education for school-age children to enhance the soft skills and overall quality - Subur Subur; Sholachuddin Al-Afghany; Vika Rahmatari; Vina Nurmalita Maylia; Nayla Anggra Agustin; Andhi Ari Anggoro (Universitas Muhammadiyah Magelang, 2023)
Kebon Wage Hamlet, Ngepanrejo Village, has a Qoryah Thoyyibah learning studio built by PPMT UNIMMA students in 2022 in collaboration with partners from LazisMU. However, there is still a problem, that there is no special training to develop the soft skills of children studying in the studio. This service activity aims to improve student character. The service is carried out using the PRA (Participatory Rural Appraisal) method, involving the community. All students and teachers in soft skills training are actively involved in the activity process. Besides that, children are also given training in soft skills and the skills to plant green beans using cotton, make wall magazines, learn to color, play puzzles, and participate in leadership activities. The results of this service include increased self-confidence in public speaking and an improved ability to articulate thoughts when speaking in public.